The pattern of Etlingera elatior cultivation in agroforestry systems and its use as traditional medicines and food by local people of Kabanjahe, North Sumatra, Indonesia - AGUS PURWOKO; HELTIMALA TURNIP; WAHYU HARYATI MASER (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Purwoko A, Turnip H, Maser WH. 2019. The pattern of Etlingera elatior cultivation in agroforestry systems and its use as traditional medicines and food by local people of Kabanjahe, North Sumatra, Indonesia. Biodiversitas 20: 1998-2003. Etlingera elatior or kecombrang (Indonesian name) is a native plant of Indonesia. In Kabanjahe, this plant is planted in agroforestry systems. The purposes of this study were to describe the pattern of Etlingera elatior cultivation in agroforestry systems, and to document the use of Etlingera elatior as medicines and food by the local people of Kabanjahe, North Sumatra. Data were collected with field observations and interviews, and the collected data were analyzed qualitatively. The results showed that kecombrang was planted in agroforestry systems in three patterns, namely (i) kecombrang, cinnamon, and coffee, (ii) kecombrang, coffee, and bamboo, and (iii) and kecombrang, avocado, and vegetables. Kecombrang has been used as medicines for cough, wound, eye problems, fever, low breast milk production, odor, and hair thinning. In addition, kecombrang has also been used as a food ingredient in ubi tumbuk, ikan arsik, sambal kincung, getah tasak telu, cipera, terong dotak, gat-gat, and gulen manuk. With this research, it is suggested that agroforestry systems be developed to improve economic benefits for the local people of Kabanjahe.